OPTIMIZATION OF SOLVENT AND CONCENTRATION OF TURMERIC (Curcuma longa Linn.) EXTRACT FOR STRIP-TEST AS BORAX DETECTION TOOL - Yulianita Pratiwi Indah Lestari,; Rizki Ramadani,; Rahmawati, Rahmawati (International Journal of Social Science, 2022)
Borax, a well-known toxic substance, had been banned as food additive in many countries, including Indonesia. Vomiting, fatigue, renal failure, cancer and even sudden death were reported as its toxic effect. There are many studies about Borax identification had been carried out, including instrumental procedures and alternative tests using natural indicator from the plants, such as turmeric. Alternative tests were low-cost, simple and easy to do. However, a certain solvent and concentration of turmeric for borax detection has not studied yet, which made a gap in borax analysis using a natural indicator. This research aims to determine the effect of turmeric solvent extraction and its concentration on borax detection results using the Turmeric Paper Test Kit. Turmeric powder was macerated with three different solvents (methanol, ethyl acetate and n-hexane) for 3 days. The highest yielded extract was methanol extract, followed by ethyl acetate and n-hexane extract. Solution of Turmeric extract in various solvents were prepared in many concentrations and dripped on paper of strip-test detection tool and leaved to dry. Borax detection was performed with dripped on strip-test detection tools, and discoloration of turmeric paper was observed. The most optimal solvent in this research is methanol extract with 10.000 ppm concentration, and discoloration to reddish-brown color